Hukum Islam Dan Multikulturalis Pluralitas dI Indonesia - Muhammad, Nova E (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2013)
This papers is reviewing about phenomenon of the multiculturalist of pluralism in Indonesia that analyzed in descriptive with Islamic law approach. This analysis was then developed on two issues, there are: 1) how the essence from the meaning of multiculturalism and pluralism in Islamic law; and 2) how the Islamic view of multiculturalism and pluralism. Simply put it can be said that pluralism the iseology of diversity. This definition would like to affirm that pluralism can be conditioned when a person believes about something ‘which is patterned much’ as a gift. This view also want to show their sincerity of every human in accepting the diversity. Pluralism is not an easy thing to be accepted just like that. In the empirical reality, plurality has always been a problem from time to the time until now, especially in responding the truth claims of each religion. Why plurality has always been a problem? The experience of inter-religious relations that have occured many years ago, probably should be a reference. In Indonesia, the occurence of disunity and conflict that have a religious background are very easy happened and sometimes it just because of a trivial issues. May even be said, almost every year there was tension, sometimes riots, result from the inter-religious sentiment. Then, it is necessary to reflect on the concept of religious pluralism in order to find positive input for diversity in Indonesia.